1979
DOI: 10.1172/jci109497
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Platelet Prostaglandin D2 Receptor

Abstract: A B S T R A C T Prostaglandin (PG)D2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
3

Year Published

1981
1981
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(29 citation statements)
references
References 14 publications
1
25
3
Order By: Relevance
“…Armstrong et al (1983) Armstrong et al (1983) on human platelets with [3H]-15(s)-9,1 l-epoxymethano-PGH2 (their value was 1,700 sites per platelet). This density was several times more than that found for the PGD2 receptor on human platelets (Siegl et al, 1979;Cooper & Ahern, 1979 Mais et al (1985a) found that U-46619 was a more potent aggregating agent than STA2 of human platelets (we also found that U-46619 was as potent as STA2), the observed order of displacing potency does not seem to fit with the biological activity. The reason for this discrepancy was not investigated in the present study but could be explained in several ways.…”
Section: Lacontrasting
confidence: 73%
“…Armstrong et al (1983) Armstrong et al (1983) on human platelets with [3H]-15(s)-9,1 l-epoxymethano-PGH2 (their value was 1,700 sites per platelet). This density was several times more than that found for the PGD2 receptor on human platelets (Siegl et al, 1979;Cooper & Ahern, 1979 Mais et al (1985a) found that U-46619 was a more potent aggregating agent than STA2 of human platelets (we also found that U-46619 was as potent as STA2), the observed order of displacing potency does not seem to fit with the biological activity. The reason for this discrepancy was not investigated in the present study but could be explained in several ways.…”
Section: Lacontrasting
confidence: 73%
“…The binding was clearly distinguishable from that to PGD synthetase or PGD2 dehydrogenase judging from the difference between the Kd value of the binding protein (33 X 10-9 M) and the Km values for PGD2 with PGD synthetase (8 X 10-6 M) (4) and PGD2 dehydrogenase (70 x 10-6 M) (6). Although PGD2 was reported to bind to some blood cells (11,23), the blood cells were excluded from the preparation by perfusion in the present study. The ratio (30%) of the specific binding to total binding with slide-mounted sections was lower than that (60-70%) with the synaptic membranes but was in the same order as that observed with P2 fraction (30%) (11).…”
Section: Discussionmentioning
confidence: 92%
“…Even though the literature indicates the DP classification of BWA868C, we independently determined the specificity of the radioligand using human-platelet homogenates, which express a constitutive DP-receptor. 35 The good correlation between the affinities of various known DP-agonists for specific [ 3 H]-BWA868C binding to human platelets and their affinities and functional potencies determined from other cell-and tissue-based assays confirmed the DP-receptor-selectivity of [ 3 H]-BWA868C.…”
Section: Discussionmentioning
confidence: 58%
“…Prior to the autoradiographic studies involving the use of [ 3 H]-BWA868C, the in vitro pharmacology of [ 3 H]-BWA868C binding to human platelets, which contain a high density of endogenous DPreceptors, 35,36 was investigated. Homogenates of human platelets were prepared in 25 mM Tris-HCl (pH 7.4) buffer containing 138 mM NaCl, 5 mM MgCl 2 , and 1 mM EDTA.…”
Section: [ 3 H]-bwa868c Binding Assaysmentioning
confidence: 99%